DETERMINANT TAX AVOIDANCE - Ismawati, Yeni Indah; Lutfillah, Novrida Qudsi (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2019)
The purpose of this research is to test and prove the existence of empirical evidence regarding the effect of company size, leverage, profitability, and sales growth on tax avoidance in basic and chemical industry companies listed on the Indonesia Stock Exchange (BEI) in 2015-2017. The research sample was 54 with data analysis techniques namely multiple regression analysis. The results show that only profitability partially affected tax avoidance. While company size, leverage and sales growth have no effect on tax avoidance. Simultaneously company size, leverage, profitability, and sales growth affected tax avoidance.